Revitalization microprojects: how the civic budget supports regeneration activities in cities: the Łódź city case study - Ślebocka, Magdalena (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: One of the distinguishing features of revitalization processes is social activation of the local community. It results directly from the very definition of revitalization, which is understood as the process of social and investment character carried out in degraded urban space which is implemented concertedly by the territorial self-government, the local community and other participants. The residents of the run-down quarters are the main beneficiaries of revitalization policy. Undertaken regeneration efforts are, first and foremost, aimed at improving their life situation. Not only grand projects are important in order to revive degraded space. It is those projects which are conducted on a microscale, which do not require substantial financial outlays and on which the inhabitants of degraded areas subjected to regeneration exert an impact that are equally significant. Undoubtedly, the civic budget and the projects submitted within its framework which supplement revitalization undertakings pose an opportunity to regenerate run-down areas on such a microscale. Aim: The purpose of the study is to evaluate the role and significance of the microprojects financed from the civic budget which fit into the revitalization process. A research hypothesis was advanced for the purpose of the article which states that the revitalization microactivities which constitute a part of the civic budget are a tool for supporting revitalization process. Results: Revitalization focuses not only on the technical aspect consisting in regeneration activities performed within the buildings themselves, but it also effectively engages local communities with the use of disposable financial means. In Łódź a systematic increase in the activation of the community dwelling in degraded area is observed. Social participation enables dialogue and cooperation among all the stakeholders, which may in turn lead to consensus and to working out the solutions satisfactory for all the parties concerned, starting from the territorial self-government which initiated the process to the inhabitants of degraded areas. One of the tools which enables local community to actively participate in the decision-making process is the civic budget. It results from the fact that the civic budget and the projects submitted within its framework are convergent with the undertaken revitalization activities. Year by year the interest in the civic budget increases and almost 50% of the projects submitted for implementation in Łódź within the analysed period of time and the spatial framework being the subject of analysis concern the activities aimed at regeneration of public space. The projects regarding public transport infrastructure, improvement of the condition of roads and pavements in revitalized areas or concerning green and recreational areas gain considerable popularity.